Factors Affecting the Quality of Financial Reports in the Government of Langkat Regency - Heri Susanto; Eka Nurmala Sari; Maya Sari (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The purpose of this study is to examine and analyze how much influence the application of Government Accounting Standards (SAP) has on the quality of the Langkat Regency Government's financial reports. The research approach uses an associative approach. The research was conducted at SKPD in the Langkat Regency Government. The population in this study amounted to 54 (fifty four) SKPD with a total of 167 (one hundred and sixty seven) respondents. By using the purposive sampling method, the number of samples taken was 31 (thirty one) SKPD with a total of 98 (ninety eight) respondents and also used as research respondents, consisting of the head of the financial sub-section as PPK-SKPD or PPK-SKPD assistants, expenditure treasurer or assistant treasurer, and Property Manager at the Service, Agency and Office within the Langkat Regency Government. This research uses data analysis method using SmartPLS.3 software which is run with computer media. Based on the research results, the application of SAP has an effect on the quality of financial reports. The quality of human resources affects the quality of financial reports. The application of SPIP affects the quality of financial reports. The use of IT affects the quality of financial reports. BMD management affects the quality of financial reports.